THE “CRIMINAL LAW OF VICTIM” AS A CRIMINAL LAW MODEL - I. A. Tretyak (Правоприменение, 2018)
The subject. The article is devoted to analysis of the basic models of criminal law and the impact of victim’s legal status on the criminal legal theory.The purpose of the paper is to substantiate the existence and the importance of “criminal law of victim” as basic model of criminal legal theory.The methodological basis of the research includes general-scientific methods (analysis and synthesis, system-structural approach) as well as academic methods (formal-legal method, method of interpretation of legal texts).Results and scope of application. The definition of the role of the victim, the importance of his legitimate interests in the implementation of criminal liability is complicated by the fact that the basic models of criminal law developed by science – “criminal law of the offender” and “criminal law of the crime” – do not consider the victim as a subject of criminal legal relations.The theoretical models of criminal law are embodied in the criminal law, specific legal rela-tions, law enforcement acts, etc., in connection with which there are specific indicators – the parameters by which it is possible to determine which model of criminal law is implemented.If the question of the criminal legal personality of the victim is controversial, in my opinion, there is no doubt that the victim is a party to the criminal law conflict, which often begins to unfold long before the crime.Conclusions. Recognizing the victim as a subject of criminal legal relations, as well as a par-ticipant in the criminal law conflict, it is possible to talk about the formation of a new model of criminal law – “the criminal law of victim”.